Religious Education as a Basic Component in the Formation of Quality Human Beings - Muid, Abdul; Mustofa, Ady Muh. Zainul (Indonesian Journal of Islamic Education and Local Culture, 2023)
The totality of humanity, idealism and religion must be produced through education if we want to become a nation and state. Teaching religion in schools is an important component in nation-building. If students are sufficiently equipped with religious teachings, they will develop into adults who are tough, disciplined, responsible, and hardworking. The research approach is qualitative with library research methods. The data analysis technique uses the Miles and Huberman data analysis model. The result of the research is that religious education also has an important position. If religious education is good, it can be guaranteed to produce quality human beings who are devoted to religion and their homeland with good principles, values ​​and norms.